Mineral absorption in relation to nutritional ecology of reindeer - Staaland, H.; Hove, K.; White, R. G. (Rangifer, 1986)
This paper addresses the way which absorption of minerals relate to nutritional ecology and mineral conservation processes. A latin square designed experiment was used to assess the effects of diet on mineral (Ca, Mg, K, Na) absorption processes in reindeer (Rangifer tarandus L.). Three male calves were fed 3 different diets: concentrate with 25% grass meal (RF-71), lichens, and a mixed diet of lichens and RF-71. Two other male calves were fed the lichen or mixed diet, supplemented with 4 g Ca/day. Ca supplementation significantly increased fecal Ca excretion, reduced the excretion of K and Mg, but had no significant effect on Na excretion. Rates of intake and fecal exretion of Ca, Mg and K were highly correlated (P
Keywords: reindeer; Rangifer; mineral absorption; digestion; calcium; Ca